Drivers of avian biodiversity in tropical agricultural landscapes - Amiruddin, Abu Hassan Din (2018)
Conversion of forest area to agriculture land is rapidly occurring in Malaysia. This landscape transformation affects biodiversity including flora and fauna. The purpose of this research was to determine the drivers of avian biodiversity in tropical agricultural landscapes such as oil palm plantation, fruit orchard and rubber tree plantation. This study had proved that the highest bird species richness was found in oil palm plantation and fruit orchard compared to rubber tree plantations. Altogether, 72 individual birds from 24 species with 15 families were found in tropical agriculture landscapes. Interestingly, the species richness of the bird was influenced by canopy coverage, light intensity and the density of tree. The drivers that influence avian species richness was canopy cover, light intensity and tree density. However, there was a significant difference in bird species richness between the oil palm plantation and rubber tree plantation as well as the fruit orchard and rubber tree plantation but there was no significance difference between the oil palm plantation and fruit orchard. Further research is required to date of the tropical agriculture landscapes for supporting biodiversity in future.